(untitled) (Praxis Educativa, 2024)
An overview study is presented regarding pedagogical practices in school Physical Education, conducted through the search and analysis of academic documents focusing on Latin America. The primary objective is to interpret the circulation of practice typologies, recurring themes, and methodologies employed in each case. To achieve this, a content analysis of 31 documents was conducted, including journal articles and works presented at scientific events. The results allow the identification of a theme of interest within the field of Physical Education in recent years, revealing four typologies of pedagogical practices organized based on theoretical dimensions that distinguish them, along with specific methodologies developed by the community of researchers.